DEVELOPING THE CAPACITY OF SOCIAL SCIENCES TEAHAERS IN BRINGING LIFE TO THE CLASS THROUGH INTESIVE CLINICAL - Faisal Faisal; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2019)
The purpose of this study is to: a) Improve the ability of physics teachers in living the classroom learning atmosphere; b) Improving the ability of social studies teachers in developing lesson plans by applying learning models that enliven the learning atmosphere in the classroom; and, c) Improving the ability of social studies teachers in increasing student activity in classroom learning activities. Data collection techniques are carried out with documentation in the form of the work of KTSP preparation, interviews and assessment analysis instruments. The results showed that there was an increase in the competence of teachers in reviving the atmosphere of learning activities in the classroom, and preparing lesson plans for the application of learning models that delight students. In cycle I, the average value of the RPP component of the application of complete learning models that can enliven the atmosphere of learning activities in the classroom, received an average score of 27.33 (good), in the second cycle the average value of the RPP component of the application models complete learning that can liven up the atmosphere of learning activities in class get a score of 32.67 (very good), an increase in the score of 5.34 is quite significant.